Increased Concentrations of Circulating Soluble MHC Class I-Related Chain A (sMICA) and sMICB and Modulation of Plasma Membrane MICA Expression: Potential Mechanisms and Correlation With Natural Killer Cell Activity in Systemic Lupus Erythematosus - Hervier, Baptiste; Ribon, Matthieu; Tarantino, Nadine; Mussard, Julie; Breckler, Magali; Vieillard, Vincent; Amoura, Zahir; Steinle, Alexander; Klein, Reinhild; Kötter, Ina; Decker, Patrice (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is a severe autoimmune disease of unknown etiology. The major histocompatibility complex (MHC) class I-related chain A (MICA) and B (MICB) are stress-inducible cell surface molecules. MICA and MICB label malfunctioning cells for their recognition by cytotoxic lymphocytes such as natural killer (NK) cells. Alterations in this recognition have been found in SLE. MICA/MICB can be shed from the cell surface, subsequently acting either as a soluble decoy receptor (sMICA/sMICB) or in CD4+ T-cell expansion. Conversely, NK cells are frequently defective in SLE and lower NK cell numbers have been reported in patients with active SLE. However, these cells are also thought to exert regulatory functions and to prevent autoimmunity. We therefore investigated whether, and how, plasma membrane and soluble MICA/B are modulated in SLE and whether they influence NK cell activity, in order to better understand how MICA/B may participate in disease development. We report significantly elevated concentrations of circulating sMICA/B in SLE patients compared with healthy individuals or a control patient group. In SLE patients, sMICA concentrations were significantly higher in patients positive for anti-SSB and anti-RNP autoantibodies. In order to study the mechanism and the potential source of sMICA, we analyzed circulating sMICA concentration in Behcet patients before and after interferon (IFN)-α therapy: no modulation was observed, suggesting that IFN-α is not intrinsically crucial for sMICA release in vivo. We also show that monocytes and neutrophils stimulated in vitro with cytokines or extracellular chromatin up-regulate plasma membrane MICA expression, without releasing sMICA. Importantly, in peripheral blood mononuclear cells from healthy individuals stimulated in vitro by cell-free chromatin, NK cells up-regulate CD69 and CD107 in a monocyte-dependent manner and at least partly via MICA-NKG2D interaction, whereas NK cells were exhausted in SLE patients. In conclusion, sMICA concentrations are elevated in SLE patients, whereas plasma membrane MICA is up-regulated in response to some lupus stimuli and triggers NK cell activation. Those results suggest the requirement for a tight control in vivo and highlight the complex role of the MICA/sMICA system in SLE.